2002
DOI: 10.1021/ma001716h
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State 13C NMR Study of Accelerated-Sulfur-Vulcanized 13C-Labeled ENB−EPDM

Abstract: Accelerated-sulfur-vulcanized 13 C-labeled EPDM with and without carbon black and extender oil was analyzed using 13 C solid-state NMR to determine the chemical structure of the network. Highresolution solid-state 13 C NMR reveals that sulfur cross-linking takes place at the allylic positions of the ENB independent of the presence of carbon black and oil. From the integrated intensities of the 13 C signals, the conversion of ENB into a cross-link can be quantitatively determined during the vulcanization proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 22 publications
1
28
0
2
Order By: Relevance
“…2(d)]. Analogous thiophene oxidation products were reported by Hahn et al11 for 2,3‐dimethyl‐2‐butene vulcanizates and by Winters et al13 for sulfur‐based cures of ethylene–propylene–diene monomer (EPDM). The possibility that thiophene could originate from the reaction of a conjugated diene ( 2 ) with sulfur14 was eliminated when these reagents were heated to 140 °C for 20 min without 5 or its cyclic precursors being produced.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…2(d)]. Analogous thiophene oxidation products were reported by Hahn et al11 for 2,3‐dimethyl‐2‐butene vulcanizates and by Winters et al13 for sulfur‐based cures of ethylene–propylene–diene monomer (EPDM). The possibility that thiophene could originate from the reaction of a conjugated diene ( 2 ) with sulfur14 was eliminated when these reagents were heated to 140 °C for 20 min without 5 or its cyclic precursors being produced.…”
Section: Resultssupporting
confidence: 61%
“…The prolonged heating of 2,3‐dimethyl‐2‐butene‐based disulfides to 150 °C is reported to yield thiophene in addition to 2,3‐dimethyl‐2‐butene and H 2 S 11. Similarly, Winters et al13 characterized a thiophene reversion product of ethylidenenorbornene‐derived allylic sulfides found in EPDM systems. Although the mechanism of allylic sulfide oxidation is not known, the dehydrocyclization of polysulfides at elevated temperatures has been well established 32.…”
Section: Discussionmentioning
confidence: 95%
“…Solid‐state 13 C NMR of 13 C‐labeled ENB‐EPDM, which was sulfur vulcanized for prolonged times (120 min at 150°C or for 30 min. at 180°C) has shown that decrosslinking occurs and a cyclic thiophene species (Scheme ) is formed 37. This suggests that the scission of the CS bond of one alkenylsulfide unit of the sulfur crosslink occurs and that a new CS bond is formed at the other allylic position of the second alkenylsulfide unit.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, because of the double bond outside the macromolecular chain of the backbone, a very high stability, both at high temperatures and in the presence of oxidizing agents, is expected. The formation of carbonyls at C‐5 and/or C‐8 of ENB–EPDM due to oxidation was shown to be linked to the accelerated sulfur vulcanization of EPDM 22. To summarize, with all of the vulcanization issues previously pointed out taken into consideration, the basic reaction scheme represented in Figure 1 can be adopted.…”
Section: Vulcanization Of Epdm With Accelerated Sulfur Experimental mentioning
confidence: 99%